2010
DOI: 10.1002/btpr.463
|View full text |Cite
|
Sign up to set email alerts
|

LPS removal from an E. coli fermentation broth using aqueous two‐phase micellar system

Abstract: In biotechnology, endotoxin (LPS) removal from recombinant proteins is a critical and challenging step in the preparation of injectable therapeutics, as endotoxin is a natural component of bacterial expression systems widely used to manufacture therapeutic proteins. The viability of large-scale industrial production of recombinant biomolecules of pharmaceutical interest significantly depends on the separation and purification techniques used. The aim of this work was to evaluate the use of aqueous two-phase mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
0
23
0
2
Order By: Relevance
“…TX-114 based phase separation was shown to be an efficient, simple and cost-effective strategy to significantly reduce or even eliminate endotoxin contamination from biological preparations [9, 1618, 2023, 26, 32]. Despite the scientific need for LPS removal to establish the immunological activity of natively folded proteins, only few studies reported on the experimental conditions that affect the efficiency of endotoxin removal from protein extracts using TX-114.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TX-114 based phase separation was shown to be an efficient, simple and cost-effective strategy to significantly reduce or even eliminate endotoxin contamination from biological preparations [9, 1618, 2023, 26, 32]. Despite the scientific need for LPS removal to establish the immunological activity of natively folded proteins, only few studies reported on the experimental conditions that affect the efficiency of endotoxin removal from protein extracts using TX-114.…”
Section: Discussionmentioning
confidence: 99%
“…A previously published TX-114 based LPS extraction protocols [25, 26] was modified to optimize for LPS removal and removal of remaining TX-114. TX-114 (Amresco, cat.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, there unquestionably can be toxicity associated with the bacterial lysis products that are produced in the course of phage-product manufacturing, potentially including bacterial exotoxins if those are generated by the bacteria used to produce phages. Also of concern is endotoxin that is solubilized upon lysis of Gram-negative bacteria [136, 140142]. Generation of these lysis products in vivo , during treatment, is an issue associated with any lytic antibacterial and certainly should be taken into account during the design of phage therapy protocols and/or avoided via the use of lysis defective phages [139, 143].…”
Section: Virion-body Interactionsmentioning
confidence: 99%
“…Lopes et al (74) demonstrate the LPS removal efficiency of this system from a fermentation broth of recombinant E. coli producing GFP. This system was capable of, while extracting GFP at rates superior to 90%, removing more than 99,5% of LPS from the sample (75). Liu et al (76) studied the partition behavior of bacteriophages (such as X174, P22, and T4) on micellar ATPSs using n-decyl tetra (ethylene oxide) (C 10 E 4 ) as surfactant.…”
Section: Extraction and Purification Of Biomolecules And Bioparticlesmentioning
confidence: 99%